Acute toxicity of Piper sarmentosum aqueous extract on haematology and liver profile in female Spragur Dawley rats - Mohd Zainudin, Maizura; Zakaria, Zaiton; Megat Mohd Nordin, Nor Anita; Othman, Faizah (2010)
Experimental studies showed that Piper sarmentosum has a variety of beneficial effect. It was demonstrated that Piper sarmentosum showed a significant anti-neoplastic hypoglycaemic, antifungal and anti malarial effects. Previous studies have shown that Piper sarmentosum surpressed the inflammatory response and increase nitric oxide production in human umbilical vein endothelial cells. Piper sarmentosum also has a significant antisclerotic property and it improves antioxidant status in the blood and tissues. despite the extensive usage and studies of this herb, no comprehensive study on its toxicity effects has been reported. Furthermore, in order to embark on human studies, a comprehensive toxicity study is a requirement. Thus, the present study was carried out to determine the general behavior, haematological, biochemical and histological toxicity of the aqueous extract of Piper sarmentoosum leaves after acute oral dosing in rats, with the aim to obtaion a comprehensive information on the safety of Piper sarmentosum and provide the guidance for selecting a safe dose of Piper sarmentosum in its use in medical practice in human. The aqueous extract of the leaves of Piper sarmentosum was admiminstered to five femalr Sprague Dawley rats in single high dose of 5g/kg by oral gavage. The rats's general behavior, adverse effects and mortality were observed for 14 days. Selected haematological and biochemical parameters and histology were determined after 14 days. The LD50 of an aqueous of the leaves of Piper sarmentosum was found to be more than 5g/kg body weight in rats. The general observations showed no signs of toxicity. The haematology and liver profiles an histology of the liver examinations revealed no signs of toxicity. It was concluded that the aqueous extract of Piper sarmentosum has no toxic effect on female Sprague Dawley rats.